Perkembangan Pendidikan Indonesia: Evaluasi Potensi Implementasi Merdeka Belajar - Putri, Shena Ananda; Asbari, Masduki; Hapizi, Muhamad Zikri (Journal of Information Systems and Management (JISMA), 2024)
The purpose of this study is to determine whether Indonesia is ready for self-directed learning. This study utilizes a qualitative descriptive method, employing note-taking to gather data by listening to the oral narration from the MetroTV YouTube channel video titled "Townhall - Is Indonesia Ready for Self-Directed Learning?" presented therein. The study's findings explain that the concept of Self-Directed Learning is an effort to transform education in Indonesia, encouraging students to transition from rote memorization-based approaches to enhancing critical thinking, creativity, independence, and the values of Pancasila. This concept has garnered diverse opinions and faced challenges, particularly in the context of the COVID-19 pandemic. Success measurement for this program involves various indicators, such as student enthusiasm and teacher readiness, but also involves issues related to budget constraints and uneven digital access. There is a growing awareness of the need for participation and dialogue among various stakeholders to refine and implement the Self-Directed Learning concept. This educational transformation requires commitment and collaborative efforts from all parties and has significant long-term impacts.